PCB Congener Specific Oxidative Stress Response by Microarray Analysis using Human Liver Cell Line - De, Supriyo (2010)
In this study we have examined the effect of exposure to different congeners of PCBs and their role in oxidative stress response. A metabolically competent human liver cell line (HepG2) was exposed with two prototype congeners of PCBs: coplanar PCB-77 and non-coplanar PCB-153. After the predetermined times of exposure (0-24 hours) at 70μM concentration, the HepG2 cells showed significant apoptotic changes by fluorescent microscopy after 12 hours of exposure. Gene set enrichment analysis (GSEA) identified oxidative stress as the predominant enrichment. Further, paraquat assay showed that PCB congeners lead to oxidative stress to different extents, PCB-77 being more toxic. This study, with emphasis on all recommended microarray quality control steps, showed that apoptosis was one of the most significant cellular processes as a result of oxidative stress, but each of these congeners has a unique signature gene expression, which was further validated by Taqman real time PCR and immunoblotting. The pathways involved leading to the common apoptotic effect were completely different. Further in-silico analysis showed that PCB-153 most likely acted through the TNF receptor, leading to oxidative stress involving metallothionein gene families, and causing apoptosis mainly by the Fas receptor signaling pathway. In contrast, PCB-77 acted through the aryl hydrocarbon receptor. It induces oxidative stress through the involvement of cytochrome P450 (CYP1A1) leading to apoptosis through AHR/ARNT pathway.